1974
DOI: 10.1677/joe.0.0610273
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sex and Age on the Cortisol Content of Peripheral Tissues and Adrenal Glands in the Guinea-Pig

Abstract: SUMMARY The influence of age and sex on the cortisol content of adrenals, liver, kidney, lung, heart, spleen, muscle, cerebrum, brain stem and blood was studied in white guinea-pigs. In prepuberal animals no significant difference between sexes was found in the cortisol content of different tissues. In adult female animals, the blood cortisol level was significantly higher than in the male animals. Significantly more cortisol was found in kidneys of adult male than of female animals. In adult guinea-pigs, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

1976
1976
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…Females tended to have higher plasma cortisol concentrations than did males. A similar gender difference has been observed in mature guinea pigs (Fazekas, Homoki, & Teller, 1974), but is unusual for younger animals of this species (Dalle & Delost, 1974;Dalle, El Hani, & Delost, 1980;Fazekas et al, 1974). We also found that male infants vocalized more than did females during exposure to the novel environment in Experiment 3.…”
Section: Discussionsupporting
confidence: 87%
“…Females tended to have higher plasma cortisol concentrations than did males. A similar gender difference has been observed in mature guinea pigs (Fazekas, Homoki, & Teller, 1974), but is unusual for younger animals of this species (Dalle & Delost, 1974;Dalle, El Hani, & Delost, 1980;Fazekas et al, 1974). We also found that male infants vocalized more than did females during exposure to the novel environment in Experiment 3.…”
Section: Discussionsupporting
confidence: 87%
“…Some other reports on cortisol levels in conscious, non-stressed guinea-pigs have given values lower thati those in this study. Blood cortisol concentrations in the present study were 19-3 /u,g/100 ml for males and 31-8 fig/100 ml for females compared with Malinowska and Nathanielsz's (1974) value for male plasma of 8-4 /Ag/100 ml and that of Fazekas, Homoki and Teller (1974) of 7-5 fig/lOO ml plasma for males and 12-6 /i,g/100 ml plasma for females. Speculative reasons for this discrepancy in cortisol values could include genetic differences in corticosteroid synthesis or metabolism, as has been demonstrated in guinea-pigs by Burstein, Kimbal and Bhavnani (1963) or strain differences in plasma corticosteroid-binding capacity as has been mentioned in the review by Shire (1974).…”
Section: Disgussioncontrasting
confidence: 49%
“…Such a dimorphism develops during the period of puberty ) and occurs also in the adult animal with differences in plasma cortisol levels (Fazekas et al 1974), in cortisol-binding affinities (Diamond, Rust & Westphal, 1969) and in cortisol catabolism (Greiner, Kramer & Colby, 1976;Manin & Delost, 1977). Our present study has shown that testosterone alone is involved in the induction of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…In guinea-pigs, sexual dimorphism has been observed with lower plasma levels of cortisol in male than in female adult animals (Fazekas, Homoki & Teller, 1974;Manin & Delost, 1977) and during puberty (El Hani & Delost, 1974). Since plasma concentrations of cortisol represent a balance between adrenal input to and clearance from the circulation, information is required concerning the metabolic clearance rate (MCR) of corticosteroids.…”
Section: Introductionmentioning
confidence: 99%